Risālat al-Sheikh Asnāwī al-Quds al-Jāwī: Rebuttal of Jawi Ulama against Fatwa of the Meccan Ulama - Rohmana, Jajang A. (Studia Islamika, 2023)
This article is carried out to discuss the rebuttal of Jawi ulama, K.H. Raden Muḥammad Asnawi Kudus (1861-1959), against the fatwa of the muftī of Mecca, Sheikh ‘Abdullāh al-Zawāwī (1850-1925), in the early twentieth century. Asnawi’s rebuttal was written in an Arabic manuscript from Banyuwangi entitled Risālat al-Sheikh Asnawī al-Quds al-Jāwī and digitized by the DREAMSEA project DS 0042 00001. The pages contain rebuttal of Asnawi against al-Zawāwī’s fatwa regarding the legal status of reading hagiography or manāqib of Sheikh ‘Abd al-Qādir al-Jaylānī (1078-1166). The manuscript shows the initial response of traditionalist ulama of Jawi to the issue of modernist Islam discussed in the Malay-Indonesia archipelago. Asnawi strongly denied the Meccan muftī’s fatwa, which is influenced by the ideas of reformist-modernist Islam. This debate marks the dynamics of the social-intellectual environment of Muslims in Mecca and Southeast Asia in the early twentieth century.